A Comparative Interventional Study of Effects of Silicon Oil on Peripapillary Capillary Perfusion in Patients with Rhegmatogenous Retinal Detachmentat Sms Hospital - Dr Nagendra Shekhawat; Dr Raju Beniwal (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Rhegmatogenous retinal detachment (RRD) is a vision-threatening condition often managed by pars plana vitrectomy (PPV) and silicone oil (SO) tamponade. While SO stabilizes the retina and facilitates reattachment, its impact on retinal microvasculature, particularly peripapillary capillary perfusion, remains under investigation. Optical Coherence Tomography Angiography (OCTA) enables detailed visualization of these vascular changes. This study evaluates the effects of SO tamponade and subsequent silicone oil removal (SOR) on peripapillary capillary perfusion in RRD patients. Methods: This prospective, interventional, comparative study included 112 eyes with unilateral RRD undergoing PPV and SO tamponade. Patients were examined pre-SOR and at 1 week, 1 month, and 3 months post-SOR. OCT Angiography (4.5×4.5 mm² scans) assessed peripapillary capillary perfusion globally and by sectors (superior and inferior). Best-corrected visual acuity (BCVA) and intraocular pressure (IOP) were also recorded. Statistical significance was set at p<0.05. Results: The global peripapillary perfusion improved from 42.266±0.913 pre-SOR to 42.870±0.884 at 3 months post-SOR (p<0.001). Superior and inferior perfusion segments showed similar progressive increases. BCVA improved significantly post-SOR (pre-SOR mean: 0.815±0.335 logMAR; post-SOR: 0.371±0.243; p<0.001). IOP normalized after SOR (pre: 18.670±2.002 mmHg; post: 12.348±3.382 mmHg; p<0.001). Each follow-up interval demonstrated statistically significant improvement compared to baseline and previous time points. Conclusion: Silicon Oil tamponade transiently reduces peripapillary capillary perfusion. Following SOR, peripapillary perfusion progressively recovers, accompanied by improved BCVA and normalized IOP. OCTA offers valuable insights into the microvascular dynamics and recovery following SO removal, guiding postoperative management and timing of SOR. Further studies should explore long-term vascular and functional outcomes to refine clinical decision-making for RRD management.